The Lived Experiences of Bangsamoro Social Workers: Their Journey in Achieving Inner Peace and Mental Well-Being - Lu, Grant Warren; Manapol, Epifania Melba; Hassan , Alimodin (Asean Social Work Journal, 2024)
The study focused on Bangsamoro social workers' journey to achieve inner peace and well-being in conflict-stricken and violent communities. It described their experiences, challenges encountered, self-care approaches, and lessons learned. The study employed a descriptive research design as it was seen as suitable to generate narratives from 12 Bangsamoro social workers through purposive and snowball sampling. The study utilized a transcendental phenomenological approach and followed the rigorous data collection and analysis following Colaizzi's seven steps of analyzing the narratives of the research participants.  The study's key findings are threats and aggressive complaints, delayed salaries and insufficiency of allowances, non-performance of family roles, and other challenges encountered. They are still capable of achieving their inner peace and well-being through self-initiated and peers, family, and faith-motivated self-care initiatives, which allow them to pause from their heavy workloads, manage their stressors into manageable parts, find better solutions to their problems, and regain their motivation to continue their work. This journey of Bangsamoro social workers implied that they could not achieve inner peace and well-being alone. Several individuals should deal with it collaboratively by influencing negative or positive experiences. It also implied that for social work practice to be efficient and progressive—the institutional mechanisms of MSSD-BARMM and other social welfare offices, the programs implemented, and the social work education should be context-based and culturally responsive.n the years, the deaf community in Vinh Long province has had to confront issues of harassment and sexual abuse due to their disabilities. Unfortunately, the majority of the deaf population lacks full awareness of harassment and sexual abuse, often misunderstanding behaviors such as teasing and unwanted touching as not constituting sexual harassment. This article focuses on analyzing the awareness of the deaf community in Vinh Long province, examining aspects such as understanding of sexual harassment behaviors and awareness of responses to harassment.